2009
DOI: 10.1128/aac.00209-09
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-Lipid Huge Toroidal Pore, a New Antimicrobial Mechanism Mediated by a Lactococcal Bacteriocin, Lacticin Q

Abstract: Lacticin Q is a pore-forming bacteriocin produced by Lactococcus lactis QU 5, and its antimicrobial activity is in the nanomolar range. Lacticin Q induced calcein leakage from negatively charged liposomes. However, no morphological changes in the liposomes were observed by light scattering. Concomitantly with the calcein leakage, lacticin Q was found to translocate from the outer to the inner leaflet of the liposomes, after it initially bound to the membrane within 2 s. Lacticin Q also induced lipid flip-flop.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(95 citation statements)
references
References 39 publications
1
92
0
1
Order By: Relevance
“…It causes membrane permeabilization of strains without need of any specific receptors [61]. It forms a huge toroidal spore (HTP) causing leakage of intracellular components and large molecules which results in the cell death.…”
Section: Lacticin Qmentioning
confidence: 99%
“…It causes membrane permeabilization of strains without need of any specific receptors [61]. It forms a huge toroidal spore (HTP) causing leakage of intracellular components and large molecules which results in the cell death.…”
Section: Lacticin Qmentioning
confidence: 99%
“…On the other hand, the unique killing mechanism of lacticin Q, a leaderless bacteriocin, has been well characterized (Yoneyama et al 2009b). While most bacteriocins require a docking molecule for their antimicrobial action, lipid II for nisin A and other lantibiotics, and mannose ABC transporter, MptD, for pediocin PA-1/AcH and its homologue bacteriocins, lacticin Q has been found to cause high-level membrane permeabilization of target strains without the need of any specific receptors (Yoneyama et al 2009a).…”
Section: Class Iid Bacteriocins (Miscellaneous Bacteriocins)mentioning
confidence: 99%
“…thereby causing cell death (Yoneyama et al 2009b). It has been shown that the mechanism of HTP formation starts with the electrostatic interaction of the cationic lacticin Q molecules and the negatively charged membranes.…”
Section: Class Iid Bacteriocins (Miscellaneous Bacteriocins)mentioning
confidence: 99%
See 2 more Smart Citations